Persepsi Anak Usia Dini terhadap Teman Sebaya Berkebutuhan Khusus di Lembaga PAUD Sekolah Sukma Nusa Bangsa - Lala Anoez; Nur Rahmiyati Luawo; Sofia K. Djafar; Tira I. Talangani (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
This research aims to reveal the perception of early childhood towards peers with special needs in the inclusive PAUD institution. Early childhood perception is an important aspect in supporting the creation of a friendly, inclusive, and empathetic learning environment. The research method used is a descriptive qualitative approach with observation techniques and semi-structured interviews with children and teachers in inclusive PAUD institutions. The results showed that most early childhood children had a positive perception of peers with special needs, such as showing an attitude of accepting, helping, and playing together without discrimination. In addition, teachers have a significant role in shaping children's understanding through habituating positive behavior, instilling equality values, and providing concrete examples in daily interactions. A supportive learning environment, collaborative play activities, and warm communication between teachers and children also contribute to the development of empathy and tolerance. This research emphasizes the importance of an inclusive pedagogical approach to cultivate children's character from an early age, so that they grow up to be more sensitive, caring, and respectful individuals in social life.